Charting the path to a sustainable, competitive and green industry in an era of rapid change: proposing a research agenda - Andreas Wallo; Jason Martin; Mattias Elg; Ulrika Harlin; Ida Gremyr; Nina Bozic; Katrin Skagert; Anna Williamsson (Cogent Business & Management, 2024)
Global labor market shifts have spurred the need for innovations and adaptations in workplace norms. This evolution demands a workforce with technical and soft skills to meet sustainability and industry advancements. The paper aims to elucidate the complex challenges related to the ambition to develop a socially sustainable, competitive, and green industry subjected to an accelerating pace of change. It outlines the findings of a Delphi study conducted in Sweden, which integrated workshops, interviews, and surveys with experts from various sectors to identify 14 key challenges. These challenges were synthesized into five themes: innovative competence supply management practices, resilient organizations and production systems, analytics for improvement and learning, socially sustainable work, and green transformation practices. The study provides a set of propositions within these themes, offering a strategic roadmap for future research to foster the growth of industries that are socially responsible, competitive, and committed to environmental sustainability. A practical implication of the study is the recognition of the larger competence ecosystem of which industrial companies are a part. This community must work together to create the knowledge needed to manage the shift to a green, sustainable, and digital working life.
Keywords: 650; industrial transformation; green transition; competence supply management; social sustainability; Delphi study